Analysis and quantification of damage in polymer composite materials - Durão, Luís Miguel (2018)
The specific characteristics of composite materials, like carbon fibre reinforced plastics, have been leading to their rising importance and widespread use. As these parts are normally produced in a nearnet shape, secondary operations, like drilling, are necessary prior to their assembly in complex structures. It is still difficult to define a machining process that enables free damage holes, due to the peculiar laminar nature of these materials. So, the definition of a drilling process that minimizes delamination and increases reliability in produced parts combined with satisfactory cost and productivity is still of major importance in the composites manufacturing industry. In this paper two sets of unidirectional coupons from plates with carbon fibre as reinforcement and epoxy resin as matrix, are drilled using five different drilling tool strategies and two feed rates for uneven damage extension. One of the strategies is the use of a pre-drilling option. Then the delamination is assessed using enhanced radiography and, finally, two diverse mechanical tests are performed on the resulting coupons: three point bending and pin bearing. The results allowed establishing and modelling, with the help of statistical tools, the relations between the damaged area caused by drilling and the material’s mechanical resistance. The bending resistance does not vary greatly with the damage area. On the other hand, the bearing resistance decreases with the increase of the damaged area.